Intestinal Epithelial Cell-Derived Extracellular Vesicles Modulate Hepatic Injury via the Gut-Liver Axis During Acute Alcohol Injury - Lamas-Paz, Arantza; Morán, Laura; Peng, Jin; Salinas, Beatriz; López-Alcántara, Nuria; Sydor, Svenja; Vilchez-Vargas, Ramiro; Asensio, Iris; Hao, Fengjie; Zheng, Kang; Martín-Adrados, Beatriz; Moreno, Laura; et al. (Frontiers in Pharmacology, 2020)
Binge drinking, i.e., heavy episodic drinking in a short time, has recently become an alarming societal problem with negative health impact. However, the harmful effects of acute alcohol injury in the gut-liver axis remain elusive. Hence, we focused on the physiological and pathological changes and the underlying mechanisms of experimental binge drinking in the context of the gut-liver axis. Eight-week-old mice with a C57BL/6 background received a single dose (p.o.) of ethanol (EtOH) [6 g/kg b.w.] as a preclinical model of acute alcohol injury. Controls received a single dose of PBS. Mice were sacrificed 8 h later. In parallel, HepaRGs and Caco-2 cells, human cell lines of differentiated hepatocytes and intestinal epithelial cells (IECs), respectively, were challenged in the presence or absence of EtOH [0-100 mM]. Extracellular vesicles (EVs) isolated by ultracentrifugation from culture media of IECs were added to hepatocyte cell cultures. Increased intestinal permeability, loss of zonula occludens-1 (ZO-1) and MUCIN-2 expression, and alterations in microbiota –increased Lactobacillus and decreased Lachnospiraceae species - were found in the large intestine of mice exposed to EtOH. Increased TUNEL-positive cells, infiltration of CD11b-positive immune cells, pro-inflammatory cytokines (e.g., tlr4, tnf, il1β), and markers of lipid accumulation (Oil Red O, srbep1) were evident in livers of mice exposed to EtOH, particularly in females. In vitro experiments indicated that EVs released by IECs in response to ethanol exerted a deleterious effect on hepatocyte viability and lipid accumulation. Overall, our data identified a novel mechanism responsible for driving hepatic injury in the gut-liver axis, opening novel avenues for therapy.